Evaluation of Syringe Feeding Compared to Bottle Feeding for the Transition from Gavage Feeding to Oral Feeding in Preterm Infants - Birgül Say; Mehmet Büyüktiryaki; Nilüfer Okur; Gülsüm Kadıoğlu Şimşek; Fuat Emre Canpolat; Nurdan Uraş; Şerife Suna Oğuz (Galenos Yayinevi, 2019)
Aim:Syringe feeding is a good alternative to a nursing supplementer when breastfeeding is not possible.Materials and Methods:This study was conducted at a level 2 neonatal intensive care unit in the Zekai Tahir Burak Maternity Teaching Hospital in a comparative and descriptive clinical study pattern. The study was carried out with 47 preterm infants in a syringe-fed group (SG) and 56 preterm infants in a bottle-fed group (BG). Primary outcomes were time of transition from gavage feeding to full oral feeding time of transition from tube to breastfeeding, and hospitalization time. Secondary outcomes were body weight at discharge (g), daily body weight gain (g/days) and gastro-intestinal intolerance symptoms during the transition period.Results:Mean gestational ages were 29.82±2.03 vs 28.18±1.56 weeks (p=0.24) and mean birth weights were 1,150.31±232.29 vs 1,016.87±186.64 g (p=0.72) in the SG and BG groups, respectively. One hundred and three infants receiving gavage feeding with gestational ages ranging from 26 to 32 weeks were evaluated for full oral feeding start time. Syringe-fed preterm infants had a mean of 40.45±19.50 days and bottle-fed infants had a mean of 53.81±16.97 days (p>0.05). The time to transition to breastfeeding (42.54±21.21 days) and time to discharge (54.48±26.92 days) in the SG was significantly shorter compared to the BG (50.45±15.95, 67.21±22.07, respectively) (p<0.05).Conclusion:We found that preterm infants for whom feeding with a syringe was used as a reinforcement in addition to orogastric feeding switched to full breastfeeding in a shorter time compared to infants who were fed by bottle. From these results, we recommend syringe feeding as a transitional method prior to breastfeeding for preterm infants during hospitalization.